Demographic Aspects and Dynamics of the Spread of COVID-19: Systematic Review Studies - Firda Islamaya Farhan; Al Yuda; Rantika Wulandari; Juliana; Putri Wardani; Putri Tipa Anasi; Diah Trismi Harjanti; Jagad Aditya Dewantara; Nuraini Astriati (Jurnal Kewarganegaraan, 2020)
Abstract Demographics are one of the aspects most affected by the dynamics of COVID-19. The increase in the number of deaths to migration trends are aspects that are affected by COVID-19. However, it is not only influenced, demographic aspects can also be a determinant that affects the dynamics of the spread of COVID-19 globally. This study uses a systematic review method that collects relevant journals to be analyzed and studied regarding the causal relationship that arises between demographic trends and the dynamics of COVID-19. The results of the journal analysis show that there is a two-way relationship between demographic trends and the dynamics of COVID-19 which influence each other. Keywords: COVID-19, Demography, Systematic Review